HOW DO SHALLOT PRICE FLUCTUATIONS COMPARE BETWEEN MARKETS IN KUPANG AND MATARAM DURING AND AFTER THE COVID-19 PANDEMIC? - Nendissa D.R.; Pong M.S.; Levis L.R.; Pellokila M.R.; Bano M.; Elvani S.; Lerik M.D.C.; Tamelan P.G. (Russian Journal of Agricultural and Socio-Economic Sciences)
Shallots are a key commodity in Indonesia and play a significant role in household consumption and economic stability. This study aims to: 1) analyze shallot price trends in Mataram and Kupang during the pandemic and post-pandemic periods, 2) assess the degree of price fluctuations in these regions, and 3) compare the variability of shallot prices between the two periods. The research utilizes secondary time-series data spanning from January 2020 to December 2023. The results show significant price fluctuations during and after the pandemic, with CV values exceeding 9%, indicating high variability. In Kupang, the CV increased from 19.16% during the pandemic to 31.62% post-pandemic, while in Mataram, it rose from 16.84% to 26.26%.